2007
DOI: 10.1086/521231
|View full text |Cite
|
Sign up to set email alerts
|

The Tennessee State University Automatic Spectroscopic Telescope: Data Processing and Velocity Variation of Cool Giants

Abstract: This paper discusses data reduction for an echelle spectrograph we have developed for an automatic telescope at Tennessee State University and are using to monitor radial velocities and line profiles of cool giant and supergiant stars. Although our approach to data reduction is rather conventional, we discuss flatfielding and extraction of velocities in ways that should be of general interest, establish a transformation to the IAU radial velocity system (ϩ0.35 ‫ע‬ 0.09 km s Ϫ1 ), and determine the external pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(58 citation statements)
references
References 43 publications
(36 reference statements)
1
57
0
Order By: Relevance
“…They derived M bol = −4.42, and estimated a mass of this object of 7.0-7.9 M . Their heliocentric radial velocity value of −42 km s −1 is in excellent agreement with other measurements in the literature (De Medeiros et al 2002;Valdes et al 2004;Eaton & Williamson 2007). Earlier studies of the stellar parameters found quite diverse results: van Paradijs (1973) measured a similar T eff = 4100 K, but a general overabundance of heavy elements by a factor of 1.6, while Luck & Bond (1980) derived for almost the same effective temperature a metallicity of [Fe/H] = −0.2.…”
Section: Hd 225212 K3 Isupporting
confidence: 85%
“…They derived M bol = −4.42, and estimated a mass of this object of 7.0-7.9 M . Their heliocentric radial velocity value of −42 km s −1 is in excellent agreement with other measurements in the literature (De Medeiros et al 2002;Valdes et al 2004;Eaton & Williamson 2007). Earlier studies of the stellar parameters found quite diverse results: van Paradijs (1973) measured a similar T eff = 4100 K, but a general overabundance of heavy elements by a factor of 1.6, while Luck & Bond (1980) derived for almost the same effective temperature a metallicity of [Fe/H] = −0.2.…”
Section: Hd 225212 K3 Isupporting
confidence: 85%
“…From 2011 November through 2014 November, we acquired 56 high-quality spectra of NP Per with the Tennessee State University 2 m Automatic Spectroscopic Telescope (AST) and a fiber-fed echelle spectrograph (Eaton & Williamson 2007) at Fairborn Observatory in southeast Arizona. Of these spectra, 55 were suitable for radial velocity measurements.…”
Section: Spectroscopic Observations and Orbitsmentioning
confidence: 99%
“…T3 is one of eight automatic telescopes operated by Tennessee State University at Fairborn for automated photometry, spectroscopy, and imaging (Henry 1995(Henry , 1999Eaton et al 2003;Eaton & Williamson 2007). T3 is equipped with a precision photometer that employs an EMI 9924B photomultiplier tube (PMT) for the successive measurements of photon count rates through Johnson B and V filters.…”
Section: Observationsmentioning
confidence: 99%